Spark plasma sintering versus hot pressing – densification, bending strength, microstructure, and tribological properties of Ti5Al2.5Fe alloys. (15th March 2018) - Yamanoglu, Ridvan; Daoud, Ismail; Olevsky, Eugene A.
ABSTRACT: Ti5Al2.5Fe alloys were fabricated by the spark plasma sintering (SPS) and hot pressing (HP) pressure-assisted sintering techniques from pre-alloyed powders with a particle size of about 200 μm. The powders were sintered at 850 °C for two different holding times (5 and 8 min) and heating rates (50 and 150°C min −1 ) at 25 MPa. The maximum relative densities were 99.70 and 98.78% for SPS and HP samples, respectively. All the alloys prepared by the SPS process had significantly higher bending strengths (1825–2074 MPa) than the alloys prepared by the HP process (648–1330 MPa). A decrease in the heating rate from 150 to 50°C min −1 enhanced the wear resistance of the Ti5Al2.5Fe alloys prepared by both the SPS and HP processes.